Unformatted text preview:

MIT OpenCourseWare http://ocw.mit.edu 16.346 Astrodynamics Fall 2008 For information about citing these materials or our Terms of Use, visit: http://ocw.mit.edu/terms.Lecture 33 Runge-Kutta Method of Numerical Integration #12 Numerical Integration dr dx dxi= v = y = yidt = dt dt i =1, 2, 3 dv ⇒dy ⇐⇒dyi = g(r) = f(x) = fi(xi )dt dt dt x(t0)= x0 y(t0)= y0 f(x0)= f0 Taylor Series Expansion dx h2 d2x h2x(t + h)= x0 + h ��+ � ���� �+ ··· = x fdt 2 0=tdt0 + hy0 + + �t0 2! t=t0 2! ···dy y(t + h)= y0 + h��h2 d2y ���h2 � + � + ··· = y + hf f dt 0 0 + + t=t0 2! dt2 t=t0 2! 0···h2 ∂f dx = y0 + hf0 + x ���� + t=t0··· 2! ∂ dt= F0y0 First Order Method Second Order Method � �� � x = x2 2 30 + hy1 0 + O(h ) x = x0 + hy0 + h f0 + O(h2) y = y h20 + hf0 + O( ) y = y0 + hf0 + 1 h22F0y + 30 O(h ) How to Avoid Calculating the Matrix F0 ∂f f(x0 + δx)= f0 + ���� δx + O[(δx)2]∂x t=t0 or for any constant p ∂f f(x0 + hpy0)= f��1�+ O(h20 + hpy0 = f0 + hpF0y0)∂x t=t0 or [f(x� 0 + hpy0) − f0]= hF0y0 + O(h2) p Hence, the second-order method is equivalent to 12 3� � x = x0 + hy0 + 2h f(x0)+ O(h ) 1 1 h f(x0 + hpy0)+ O(h3)+ h 1 − f(x0)+y = y0 2p 2p Choose p = 1 and note that f(x0) − f(x0 + hpy0)= O(h). Therefore, we have 2 x = x0 + hy0 + 12h2f(x0 + 12hy0)+ O(h3) y = y0 + hf(x0 + 12hy0)+ O(h3) with only one evaluation of the function f(x) for x = x0 + 12hy0. 16.346 Astrodynamics Lecture 330 0 1 0 0 21Equate corresponding coefficients of α0 and α� � � � 1 a = 1 1 1 b a p 2 = 1 = ⇒ = = 1 b 2 =1 p 2 In summary: x = x1 0 + hy0 + h22k + O(h3) y = y0 + hk + O(h3) k = f(x0 + 1 h2y0) Taylor Expansion using Indicial Notation and Summation Convention dxi h2 d2xi h3 d3xi h4 d4xi xi(t + h)=x i+ h + + + +dt 2! dt2 3! dt3 4! dt4 ··· 2 3 i 4 2 i = i + i h hdf hd fx hy + fi + + + 2! 3! dt 4! dt2 ···3 32 3 i j 4 i j= i + i h+ i h� ∂f dxh� d ∂fx hy fdt� dx+ + + 2! 3! ∂xj dt 4! ∂xjdt j=1 j=1 � ···h2 h3 h4 = x i + fi+ j y + hyi + fij(fiyjy k+ fi jjk jf )+2! 3! 4! ··· Taylor Expansion of a Vector Function of a Vector fi(xi + δi)= fi+ fiδj+ 1 fiδjδk+ 1 fiδjjkδkδj2 6 jk+ ··· 16.346 Astrodynamics Lecture 33 ���� ���� � � Formal Derivation of the Second-Order Method Choose a, b, p so that x = x0 + hy0 + h2 ak + O(h3) x = x0 + hy0 + 12h2α0 + O(h3) y = y0 + hbk + O(h3) ≡ y = y0 + h(α0 + 1hα1)+ O(h3)2k = f(x0 + hpy0) k = α0 + hpα1 + O(h2) where α0 = f0 and α1 = f0= F0y0 . Expand f(x0 + hpy0) in a Taylor series: ∂f ∂f δx + O[(δx)2] = f(x0 + hpy0)= f0 + +O(h2)f(x + δx)= f0 + hpy0⇒ ∂x ∂x t=t0 ��t=t0 = α0 + hpα1Then x = x0 + hy0 + h2 a(α0 + hpα1)+ O(h3) x = x0 + hy0 + 12h2α0 + O(h3) y = y + hb(α + hpα )+ O(h3) ≡ y = y + h(α + 1hα )+ O(h3)Nystr¨om’s Third Order Method Evert Johannes Nystr¨om 1925 x = x0 + hy0 + h2(a0k0 + a1k )+ O(h41) y = y40 + h (b0k0 + b1k1)+ O(h ) k0 = f(x0 + hp0y0) k1 = f(x0 + hp2 1y0 + h q1k0) Series Expansion Using Indicial Notation xi (t + h)= x i + hyi + 1h2fi + 13 h fi yj2 6j+ O(h4) i i i 12 i j 13 i j k i j 4� �� � h f + h (f + fy(t + h)= y + hf + 2jy6jky yjf )+ O(h ) k0 i = fi(x i + hp0y i)= fi + fihp0yj + 1fi (hp0yj)(hp0y k)+ O(h3)� �� � j2jkδi 0 k1 i = fi(x i + hp1y i + h2 q1k0 i )= fi[x i + hp1y i + h2 q1fi + O(h3)] δi = fi + fi(hp1yj + h2 fj)+ 1fi (hp1yj)(hp1y k)+ O(h3)1 jq12jkSeries Expansion Using Vector Notation x = x0 + hy0 + h2(12α0 + 16hα1)+ O(h4) y = y0 + h[α0 + 12hα1 + 16h2(α2 + β2)] + O(h4) k0 = f(x0 + hp0y0)= α0 + hp0α1 + 12h2 p02α2 + O(h3) k1 = f(x0 + hp1y0 + h2 q1k0)= α0 + hp1α1 + h2(21 p12α2 + q1β2)+ O(h3) Determine a0 , a1 , b0 , b1 , p0 , p1 , q1 h2(a0k0 + a1k1) ≡ h2(1α0 + 1hα1) to terms of order h3 2 6h(b0k0 + b1k1) ≡ h[α0 + 21hα1 + 61h2(α2 + β2)] to terms of order h3 Condition Equations � �� � � 1 �⎡ 1 1 ⎤� b0 � ⎡ 1 ⎤ (α ) 1 1 a0 = 21 ⎣ p0 p1 ⎦ b1 = ⎣ 12 ⎦ p0 p1 a16 2 21 p0 p1 3 (β ) q1b1 = 12 ( 13 ) 16.346 Astrodynamics Lecture 330 1 1 1 p b + p b = 1 (1 p0)b0 +(1 p1)b1 = a2 0 + a1 = 2 0 0 1 1 2 = − −⇒ p0(1 − p0)b b⇐⇒= 1 0 + p1(1 p1)1 = 1 p0a0 + p1a1 p 2 0b0 + p 2 1b1 1 = 6 6 3 −Hence a0 =(1 − p0)b0 and a1 =(1 − p1)b1 . Next, for consistency, b0 + b1 =1 ���1 1 1 p0b0 + p1b1 1 = 2 3 = �p 2= 1 �0b0 + p 2 ⇐⇒ D1b1 3��p p1 p��Expand the determinan�0 1 �� 2 20 p 2113 �=0 t � D3 = ��1 V��p0 p���1 1 = � �����andermonde determinant 1 (p1 11 2 1 2 21 �� − p0� )[ − (p0+ p1)+p0p1] = V2 L3(p0,p1)Complete � p 0 p 13 solution � �3 2Constrain��t function � �=0 �� � 1 p1 b2 1 p2 0 1 p1 p0 0 = −b1 = −q1 =−a0 =(1 − p0)b0 a1 =(1 − p1)bp1 0 − p1 p1 − p0 6 1 − p20 with p0 and p1 chosen arbitrarily subject to L (p ,p )= 1− 1 3 0 1(p3 20 + p1)+ p0p1 =0 Nystr¨om’s Third Order Algorithm with p0 =0 x = x0 + hy0 + 1h24(k0 + k1)+ O(h4) y = y0 + 1h O4(k0 +3k1)+ (h4) k0 = f(x0) k = …


View Full Document
Download Lecture Notes
Our administrator received your request to download this document. We will send you the file to your email shortly.
Loading Unlocking...
Login

Join to view Lecture Notes and access 3M+ class-specific study document.

or
We will never post anything without your permission.
Don't have an account?
Sign Up

Join to view Lecture Notes 2 2 and access 3M+ class-specific study document.

or

By creating an account you agree to our Privacy Policy and Terms Of Use

Already a member?